MateFun: Functional Programming and Math with Adolescents - Carboni, Alejandra; Koleszar, Victor; Tejera, Gonzalo; Viera, Marcos; Wagner, Javier (2018 XLIV Latin American Computer Conference (CLEI), 2018)
The MateFun project arises with the intention of approaching disciplines that intersect in the field of education, based on the transversality of information and communication technologies with respect to Engineering, Communications, Psychology, Teaching and Pedagogy. In Uruguay, computer courses are increasingly being integrated into curricular content, since learning to program seems to be part of the skills needed for today's people. However, programming in general is absent in mathematics teaching, contrary to the inherent relationship of both. In turn, according to 2015 data from the Educational Monitor of the National Administration of Public Education of Uruguay, Mathematics is the least approved subject of the basic secondary cycle. MateFun is a functional programming language, accessible from a web application, especially aimed to math functions learning. It is intended that through MateFun the learning of programming strengthens the appropriation of the concept of mathematical function, at the same through this project we seek to generate scientific evidence of the transfer or the contributions of programming learning to math. Preliminary data show that the adolescents who experimented with MateFun had similar learning to the control group in mathematical functions, but they also acquired basic knowledge of functional programming.